2020
DOI: 10.3389/fphar.2020.00958
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant and Anti-Neuroinflammatory Effects of Bangpungtongsung-San

Abstract: Bangpungtongsung-san (BTS) is a traditional Korean medicine consisting of 18 herbs, some which have antidepressant effects. Here, we used an animal model of reserpineinduced depression and lipopolysaccharide (LPS)-stimulated BV2 microglia to assess the antidepressant and anti-neuroinflammatory effects of BTS. Aside from a control group, C57BL/6 mice were administered reserpine (0.5 mg/kg) daily for 10 days via intraperitoneal injection. BTS (100, 300, or 500 mg/kg), vehicle (PBS), or fluoxetine (FXT, 20 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 51 publications
5
18
0
1
Order By: Relevance
“…Reserpine administration improves anxiety and depressive-like behaviors shown by mice staying at the edge of the space in OFT and maintaining immobility in TST and FST (Chang et al, 2015). This induced symptom effectively relieves anxiety and depressive symptoms, such as increased crossing and decreased immobility by antidepressant-like PSAP and herbal medicines (Sousa et al, 2018;Park et al, 2020). This study found that reserpineadministered mice exhibited reduced central dwelling time and entry frequency in the OFT as well as increased immobility in the TST and FST.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Reserpine administration improves anxiety and depressive-like behaviors shown by mice staying at the edge of the space in OFT and maintaining immobility in TST and FST (Chang et al, 2015). This induced symptom effectively relieves anxiety and depressive symptoms, such as increased crossing and decreased immobility by antidepressant-like PSAP and herbal medicines (Sousa et al, 2018;Park et al, 2020). This study found that reserpineadministered mice exhibited reduced central dwelling time and entry frequency in the OFT as well as increased immobility in the TST and FST.…”
Section: Discussionsupporting
confidence: 50%
“…This evidence has been applied to animal models showing depressive symptoms, and reserpine-administered animal models are being used to study the pathological symptoms of depression (Uriguen et al, 2008). Reserpine administration may affect neuroinflammation by damaging rodent nerve tissues and releasing proinflammatory cytokines such as IL-1β, IL-12, IL-6, TNF-α, and IFN-γ from the hippocampus, liver, and serum (Huang et al, 2004;Zhou et al, 2014;Park et al, 2020). In addition, brain-derived neurotrophic factor (BDNF)-Tropomyosin receptor kinase B (TrkB) signaling participates in emotional, learning, and memory regulation in the hippocampus and activates neurotrophic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Reserpine (purchased from Sigma-Aldrich, St Louis, MO, USA) was dissolved in the vehicle (phosphatebuffered saline (PBS) containing 0.1 % dimethyl sulfoxide (DMSO) and 0.3 % Tween-80) to a final concentration of 1 mg/kg. Reserpine was administered to mice intraperitoneally with a dose of 1 mg/kg/d for 3 consecutive days, according to a published paper [14] .…”
Section: Induction Of Experimental Depressionmentioning
confidence: 99%
“…13 Another study found that after antidepressant treatment in a vivo model of depression, the production of NO was decreased by inhibiting the expression of iNOS. 14 The possible mechanism is that inhibiting iNOS signaling pathway may alleviate depressive symptoms by exerting anti-inflammatory and neuroprotective effects. 15 Macrophage inflammatory protein 1α (MIP-1α) belongs to a member of the CC subfamily of chemokines and its release is considered a crucial process in the recruitment of inflammatory cells during initiation and subsequent maintenance of inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…21 The 80 patients diagnosed with depression after the first-ever acute ischemic stroke were enrolled in PSD group. The PSD group was divided into mild PSD group (8)(9)(10)(11)(12)(13)(14)(15)(16), moderate PSD group (17)(18)(19)(20)(21)(22)(23) and severe PSD group (≥ 24) according to HAMD scores. 22 During the same period, 40 non-depressed patients after the first-ever acute ischemic stroke and 40 healthy control subjects were recruited as non-PSD group and normal group, respectively.…”
mentioning
confidence: 99%